Awareness Of Applying Value Engineering In Construction Industry In Penang, Malaysia. - Pah, Sock Yong (Universiti Sains Malaysia, 2006)
This dissertation research is an initial study on the awareness of applying Value Engineering in the construction industry by using the state of Penang as a test ivcase for the model of application. Value Engineering is a tool recently developed in the field of engineering management that will allow a specific function of a project to be achieved at a reasonable cost.